Validity of Chemo-entrepreneurship Teaching Material to Analyze Students’ Cognitive in Redox Reaction - Wildana, Maula Najikh; Sumarti, Sri Susilogati; Susilaningsih, Endang; Nuryanto, Nuryanto (International Journal of Active Learning, 2022)
Chemo-entrepreneurship or CEP known as learn chemistry with an entrepreneurial approach to made products. Teachers in research school only use provided books by schools and materials on internet, so it is necessary to develop effective teaching material that fits main purpose. There also need to develop learning media to train student’s ability from interdisciplinary approaches. The aim of this research is to develop chemo-entrepreneurship teaching materials that appropriate and effective to analyze students’ cognitive. This is Research and Development method with ADDIE model. Data collection methods are by observation, questionnaires, tests, and project methods. Data analysis techniques include analysis of interview sheets, instrument validation, analysis the effectiveness of teaching materials, and analysis of questionnaire responses. The result is 87% of students pass the minimum score, means most students pass the achievement and have good cognitive abilities. There are 26 passed students and 4 not passed. Teaching materials get validity score 49 of 52. Teaching materials get positive responses from teachers with score 35 of 40 and positive responses from students with an average score of 38.53 of 48. It means that developed material book appropriate and effective to help teacher explain chemistry with interdisciplinary approaches.